Dynamic of cold-atom tips in anharmonic potentials - Menold, Tobias; Federsel, Peter; Rogulj, Carola; Hölscher, Hendrik; Fortágh, József; Günther, Andreas (Beilstein Journal of Nanotechnology, 2016)
Background: Understanding the dynamics of ultracold quantum gases in an anharmonic potential is essential for applications in the new field of cold-atom scanning probe microscopy. Therein, cold atomic ensembles are used as sensitive probe tips to investigate nanostructured surfaces and surface-near potentials, which typically cause anharmonic tip motion.Results: Besides a theoretical description of this anharmonic tip motion, we introduce a novel method for detecting the cold-atom tip dynamics in situ and real time. In agreement with theory, the first measurements show that particle interactions and anharmonic motion have a significant impact on the tip dynamics.Conclusion: Our findings will be crucial for the realization of high-sensitivity force spectroscopy with cold-atom tips and could possibly allow for the development of advanced spectroscopic techniques such as Q-control.
Keywords: anharmonic motion; cold-atom scanning probe microscopy; dephasing; dynamic mode; tip oscillation

Scanning Probe Microscopy in Nanoscience and Nanotechnology - Bhushan, B. (Springer Verlag, 2010)

(untitled) - Binnig, G.; Quate, C. F.; Gerber, C. (Phys. Rev. Lett., 1986)

(untitled) - Binnig, G.; Rohrer, H.; Gerber, C.; Weibel, E. (Appl. Phys. Lett., 1982)

(untitled) - Giessibl, F. J. (Rev. Mod. Phys., 2003)

(untitled) - Binnig, G.; Rohrer, H. (Rev. Mod. Phys., 1987)

(untitled) - Martin, P. J.; Gould, P. L.; Oldaker, B. G.; Miklich, A. H.; Pritchard, D. E. (Phys. Rev. A, 1987)

(untitled) - Xu, J. B.; Läuger, K.; Dransfeld, K.; Wilson, I. H. (Rev. Sci. Instrum., 1994)

(untitled) - Frisbie, C. D.; Rozsnyai, L. F.; Noy, A.; Wrighton, M. S.; Lieber, C. M. (Science, 1994)

(untitled) - Sugimoto, Y.; Pou, P.; Abe, M.; Jelinek, P.; Pérez, R.; Morita, S.; Custance, Ó. (Nature, 2007)

(untitled) - Davis, K. B.; Mewes, M.-O.; Andrews, M. R.; van Druten, N. J.; Durfee, D. S.; Kurn, D. M.; Ketterle, W. (Phys. Rev. Lett., 1995)

(untitled) - Anderson, M. H.; Ensher, J. R.; Matthews, M. R.; Wieman, C. E.; Cornell, E. A. (Science, 1995)

(untitled) - Greiner, M.; Mandel, O.; Esslinger, T.; Hänsch, T. W.; Bloch, I. (Nature, 2002)

(untitled) - Inouye, S.; Andrews, M. R.; Stenger, J.; Miesner, H.-J.; Stamper-Kurn, D. M.; Ketterle, W. (Nature, 1998)

(untitled) - Kraemer, T.; Mark, M.; Waldburger, P.; Danzl, J. G.; Chin, C.; Engeser, B.; Lange, A. D.; Pilch, K.; Jaakkola, A.; Nägerl, H.-C.; Grimm, R. (Nature, 2006)

(untitled) - Weinstein, J. D.; Libbrecht, K. G. (Phys. Rev. A, 1995)

(untitled) - Vuletić, V.; Fischer, T.; Praeger, M.; Hänsch, T. W.; Zimmermann, C. (Phys. Rev. Lett., 1998)

(untitled) - Fortágh, J.; Grossmann, A.; Zimmermann, C.; Hänsch, T. W. (Phys. Rev. Lett., 1998)

(untitled) - Reichel, J.; Hänsel, W.; Hänsch, T. W. (Phys. Rev. Lett., 1999)

(untitled) - Cassettari, D.; Hessmo, B.; Folman, R.; Maier, T.; Schmiedmayer, J. (Phys. Rev. Lett., 2000)

(untitled) - Folman, R.; Krüger, P.; Cassettari, D.; Hessmo, B.; Maier, T.; Schmiedmayer, J. (Phys. Rev. Lett., 2000)

(untitled) - Ott, H.; Fortágh, J.; Schlotterbeck, G.; Grossmann, A.; Zimmermann, C. (Phys. Rev. Lett., 2001)

(untitled) - Hänsel, W.; Hommelhoff, P.; Hänsch, T. W.; Reichel, J. (Nature, 2001)

(untitled) - Lin, Y.; Teper, I.; Chin, C.; Vuletić, V. (Phys. Rev. Lett., 2004)

(untitled) - Harber, D. M.; Obrecht, J. M.; McGuirk, J. M.; Cornell, E. A. (Phys. Rev. A, 2005)

(untitled) - Wildermuth, S.; Hofferberth, S.; Lesanovsky, I.; Haller, E.; Andersson, L. M.; Groth, S.; Bar-Joseph, I.; Krüger, P.; Schmiedmayer, J. (Nature, 2005)

(untitled) - Günther, A.; Kraft, S.; Kemmler, M.; Koelle, D.; Kleiner, R.; Zimmermann, C.; Fortágh, J. (Phys. Rev. Lett., 2005)

(untitled) - Obrecht, J. M.; Wild, R. J.; Antezza, M.; Pitaevskii, L. P.; Stringari, S.; Cornell, E. A. (Phys. Rev. Lett., 2007)

(untitled) - Bender, H.; Stehle, C.; Zimmermann, C.; Slama, S.; Fiedler, J.; Scheel, S.; Buhmann, S. Y.; Marachevsky, V. N. (Phys. Rev. X, 2014)

(untitled) - Gierling, M.; Schneeweiss, P.; Visanescu, G.; Federsel, P.; Häffner, M.; Kern, D. P.; Judd, T. E.; Günther, A.; Fortágh, J. (Nat. Nanotechnol., 2011)

(untitled) - Schneeweiss, P.; Gierling, M.; Visanescu, G.; Kern, D. P.; Judd, T. E.; Günther, A.; Fortágh, J. (Nat. Nanotechnol., 2012)

(untitled) - Ockeloen, C. F.; Schmied, R.; Riedel, M. F.; Treutlein, P. (Phys. Rev. Lett., 2013)

(untitled) - Hölscher, H.; Allers, W.; Schwarz, U. D.; Schwarz, A.; Wiesendanger, R. (Phys. Rev. Lett., 1999)

(untitled) - Anczykowski, B.; Cleveland, J. P.; Krüger, D.; Elings, V.; Fuchs, H. (Appl. Phys. A, 1998)

(untitled) - Hölscher, H.; Schwarz, U. D. (Int. J. Nonlinear Mech., 2007)

(untitled) - Ebeling, D.; Hölscher, H.; Fuchs, H.; Anczykowski, B.; Schwarz, U. D. (Nanotechnology, 2006)

(untitled) - Dagdeviren, O. E.; Götzen, J.; Hölscher, H.; Altman, E. I.; Schwarz, U. D. (Nanotechnology, 2016)

(untitled) - You, L.; Holland, M. (Phys. Rev. A, 1996)

(untitled) - Ott, H.; Fortágh, J.; Kraft, S.; Günther, A.; Komma, D.; Zimmermann, C. (Phys. Rev. Lett., 2003)

(untitled) - Ott, H.; Fortágh, J.; Zimmermann, C. (J. Phys. B: At. Mol. Phys., 2003)

(untitled) - Dalfovo, F.; Giorgini, S.; Pitaevskii, L. P.; Stringari, S. (Rev. Mod. Phys., 1999)

Nonlinear systems - Drazin, P. G. (Cambridge University Press, 1992)

Klassische Mechanik - Kuypers, F. (Wiley-VCH, 2010)

(untitled) - Meyer, G.; Amer, N. M. (Appl. Phys. Lett., 1988)

(untitled) - Marti, O.; Colchero, J.; Mlynek, J. (Nanotechnology, 1990)

(untitled) - Rugar, D.; Mamin, H. J.; Guethner, P. (Appl. Phys. Lett., 1989)

(untitled) - Hölscher, H.; Milde, P.; Zerweck, U.; Eng, L. M.; Hoffmann, R. (Appl. Phys. Lett., 2009)

(untitled) - Giessibl, F. J. (Appl. Phys. Lett., 1998)

(untitled) - Tortonese, M.; Barrett, R. C.; Quate, C. F. (Appl. Phys. Lett., 1993)

(untitled) - Tavassolizadeh, A.; Meier, T.; Rott, K.; Reiss, G.; Quandt, E.; Hölscher, H.; Meyners, D. (Appl. Phys. Lett., 2013)

Proceedings of the International School of Physics - Enrico Fermi - Ketterle, W.; Durfee, D. S.; Stamper-Kurn, D. M. (Making, probing and understanding Bose-Einstein condensates, 1999)

(untitled) - Federsel, P.; Rogulj, C.; Menold, T.; Fortágh, J.; Günther, A. (Phys. Rev. A, 2015)

Fundamentals of Picoscience - Günther, A.; Hölscher, H.; Fortágh, J. (Cold Atom Scanning Probe Microscopy: An Overview, 2013)

(untitled) - Fortágh, J.; Zimmermann, C. (Rev. Mod. Phys., 2007)

(untitled) - Günther, A.; Kemmler, M.; Kraft, S.; Vale, C. J.; Zimmermann, C.; Fortágh, J. (Phys. Rev. A, 2005)

(untitled) - Stibor, A.; Bender, H.; Kühnhold, S.; Fortágh, J.; Zimmermann, C.; Günther, A. (New J. Phys., 2010)

(untitled) - Günther, A.; Bender, H.; Stibor, A.; Fortágh, J.; Zimmermann, C. (Phys. Rev. A, 2009)

(untitled) - Grüner, B.; Jag, M.; Stibor, A.; Visanescu, G.; Häffner, M.; Kern, D.; Günther, A.; Fortágh, J. (Phys. Rev. A, 2009)

(untitled) - Kraft, S.; Günther, A.; Fortágh, J.; Zimmermann, C. (Phys. Rev. A, 2007)

(untitled) - Stibor, A.; Kraft, S.; Campey, T.; Komma, D.; Günther, A.; Fortágh, J.; Vale, C. J.; Rubinsztein-Dunlop, H.; Zimmermann, C. (Phys. Rev. A, 2007)

(untitled) - Wade, A. C. J.; Baillie, D.; Blakie, P. B. (Phys. Rev. A, 2011)

(untitled) - Bird, G. A. (Phys. Fluids (1958-1988), 1970)

(untitled) - Wagner, W. (J. Stat. Phys., 1992)

Molecular Gas Dynamics and the Direct Simulation of Gas Flows - Bird, G. A. (Oxford University Press, 1994)

(untitled) - Birdsall, C. K.; Fuss, D. (J. Comput. Phys., 1969)

(untitled) - Fortágh, J.; Ott, H.; Kraft, S.; Günther, A.; Zimmermann, C. (Appl. Phys. B, 2003)